Green fodder from energy forest farming - Matti Näsi (Agricultural and Food Science, 1981)
The study examined the yield, chemical composition and nutritive value of energy tree leaves under one year rotation, and considered the methods and results in the entire tree utilization. The proportion of leaves was 31 % for Salix cv. Aquatica and 16 % for S. viminalis of the total biomass yield. The dry matter yield of leaves amounted to 3—5 tn DM/ha. The average chemical composition of willow leaves was as follows: dry matter 27 %, ash 7.7 %, crude protein 19.5 %, ether extract 4.9 %, and crude fibre 14.1 %. The content of tannins was 4.1 % in willow leaves and 3.4 % in alder leaves. Fertilization had a significant effect on the ash and protein contents of willow leaves. Crude fibre content of alder leaves was higher compared to willow leaves. In vitro digestibility of willow leaves was 64 % for organic matter and pepsine-HCI soluble protein was 65 % on average. Fertilization improved the digestibility 6—8 %-units. Calcium content of willow leaves was 10g/kg DM, phosphorus 3g/kg DM and magnesium 2.8 g/kg DM. The amount of trace elements was considerably high. On account of the high content of protein and minerals willow leaves are a considerable source of feed for domestic animals or wild ruminants. The harvesting and conservation of leaves is still a technical question that has to be resolved.